Distributional Effects of Oil Price Changeson Household Expenditures : Evidence From Mali - Kpodar, Kangni (IMF Working Papers; Working Paper ;, 2006)
Using an input-output approach, this paper assesses the distributional effects of a rise in various petroleum product prices in Mali. The results show that, although rising gasoline and diesel prices affect mainly nonpoor households, rising kerosene prices are most harmful to the poor. Overall, the impact of fuel prices on household budgets displays a U-shaped relationship with expenditure per capita. Regardless of the oil product considered, highincome households would benefit disproportionately from oil price subsidies. This suggests that a petroleum price subsidy is an ineffective mechanism for protecting the income of poor households compared with a targeted subsidy.